Fulton aus Marstal: ein dänischer Schoner in Vergangenheit und Gegenwart - Crumlin-Pedersen, Ole (2002)
Since the late 1960s, concerted efforts have been made in Denmark to preserve a small selection of characteristic Nordic wooden vessels of the sailing era for posterity. Of epochal significance within this context have been the endeavours of the National Museum in Copenhagen/Roskilde with regard to the FULTON, a three-masted schooner built in Marstal in 1915 and acquired by the museum in 1970. The history of the FULTON is divided into three sections: the period of the ship’s operation under sail as a cargo vessel on the North Atlantic from 1915 to 1923, then on the Baltic by sail and engine until 1969, and since 1970 as a sailing museum ship in Danish waters with a crew of Danish youth. The present article reports on the ship’s history and on the fates of several of the persons involved with her beginnings and early phase. The story of the FULTON serves as an example of how the circumstances of shipping in the past can by conveyed to the young generation of the present, and how the members of this generation can thus develop prospects for their own futures. begutachtet Veröffentlichungsversion reviewed Published Version